Identifying risk factors for perinatal mortality from a preceding pregnancy without perinatal mortality. Issue 2 (15th April 2021) - Levi, Rinat; Pariente, Gali; Sheiner, Eyal; Wainstock, Tamar
Abstract: Objective: To identify risk factors in first pregnancy for perinatal mortality in the subsequent pregnancy. Methods: A retrospective population‐based nested case‐control study was conducted, including all women with two first singleton consecutive deliveries. Women with perinatal mortality in their first pregnancy were excluded, and cases with perinatal mortality in the second pregnancy were compared with controls who delivered a live birth. Characteristics and complications of the first pregnancy were compared between the groups using multivariable logistic models. Results: A total of 43 043 women were included in the study, 385 (0.9%) were cases. Cases, as compared with controls (live births), were younger (22.62 ± 4.0 vs 23.22 ± 4.0 years), with shorter inter‐pregnancy interval (1.38 ± 1.55 vs 1.56 ± 1.53 years), and were more likely to have the following complications in their first pregnancy: severe pre‐eclampsia (3.4% vs 1.7%), small for gestational age (12.5% vs 8.0%), preterm delivery (17.7% vs 7.8%), and congenital or chromosomal malformations (9.6% vs 5.9%). In multivariable analysis the risk for perinatal mortality was greater with each additional complication (adjused odds ratio [aOR] 1.64, 95% confidence interval [CI] 1.30–2.07, P  < 0.001; aOR 2.55, 95% CI 1.61–4.04, P  < 0.001; aOR 7.88, 95% CI 3.81–16.29, P  < 0.001 for one, two, and three or more complications, compared with no complications, respectively). Conclusion: Complications in first pregnancy ending with live birth are associated with increased risk for perinatal mortality in a subsequent pregnancy. Abstract : First pregnancy complications are associated with an increased risk for perinatal mortality in a subsequent pregnancy of women with no history of perinatal mortality.